The Singularization of History: Social History and Microhistory within the Postmodern State of Knowledge. - Sigurður, Gylif Magnússon (Journal of Social History)
The writer discusses how social history, dominated by quantitative methods of the social sciences, has failed to meet the challenges posed by postmodernism and the demands of cultural analysis. To illustrate his point, he focuses on microhistory, as representing the most effective reaction from within the field of history to the dilemma facing social history. The response of microhistory was both groundbreaking and unconventional, he explains, turning attention away from the unremitting concentration on the huge structures, large-scale processes, and big comparisons and toward the small units in society. He finds, however, that microhistory, has as yet failed to make any significant impression on contemporary historiography, and he considers various reasons for this.